Produção e qualidade pós-colheita do tomateiro em diferentes tensões de água no solo - Rodrigues, Rogério Rangel (2017)
Different tomato varieties could have different water requirements, making it essential studies about the water demand for this crop. This study aim was to evaluate the soil water tension influence on production and post-harvest quality of tomato fruits, variety Dominador F1, under drip irrigation and cultivated in greenhouse. The study was conducted in a randomized block design with four replications and the treatments were six soil water tensions as indicative of the irrigation trigger point. The pre-set tensions were 20, 45, 70, 95, 120 and 145 kPa at 20 cm depth. At 140 days after transplanting the evaluated variables were: total, commercial and non-commercial fruits production; Total, commercial and non-commercial fruit yield; Number of fruits per plant; Classification of commercial fruits; Average mass of commercial fruits; Blossom end rot incidence (%); Water use efficiency (WUE); Titratable acidity (TA); Total soluble solids (TSS); pH; Ratio total soluble solids by titratable acidity (TSS/TA); Soluble pectin; Vitamin C; Firmness; Coloration and content of macro and micronutrients of the aerial part. The results showed the highest values of commercial production and productivity, number of fruits per plant, number of large and medium fruits and average mass of commercial fruits, occurs when the soil water tension is around 20 kPa, at 0.20m depth. The different water stresses did not significantly affect titratable acidity, pH, ratio of total soluble solids by titratable acidity and soluble pectin. The water use efficiency increased up to a tension of 116.57 kPa as a function of soil water stresses. From the quality characteristics evaluated, total soluble solids, vitamin C, firmness and L* coloring index had a significant effect on soil water stress. The highest levels of macro (P and S) and micronutrients (B and Cu) at the total aerial part were obtained in the tension of 20 kPa, its value reducing linearly with the increase soil water tension.